Knowledge and Attitude of Obstructive Sleep Apnea among Dental Students in North East Penisular Malaysia - Adnan, Munirah Mohd; Kassim, Nur Karyatee; Mohd Rasid, Nur Mardhiyyah; Ibrahim, Hanim Afzan; Ramli, Rosmaliza; Ghani, Nurhafizah; Hanafi, Muhammad Hafiz (Bangladesh Journal of Medical Science, 2022)
Background: Obstructive sleep apnea (OSA) is sleep-disordered breathing that can cause morbidity and mortality.Dental students’ knowledge of sleep apnea will help them identify patients with the condition in the future. Objective: This study was conducted to determine the knowledge and attitude of OSA among undergraduate dental students in Universiti Sains Malaysia (USM). Methodology: A total of 97 undergraduate dental students participated in this study. This cross-sectional study used a self-administered and validated Obstructive Sleep Apnea Knowledge and Attitude (OSAKA) questionnaire. The questionnaire consists of 18 questions of knowledge and five questions of attitude towards OSA. Results: The mean total score of knowledge is 7.5 (SD 3.77). Meanwhile, the mean total score of attitude is 12.0 (SD 2.22). Most of the students (74.2%) knew that majority of patients with OSA snored. However, only 14.4% knew uvulopalatopharyngoplasty is the curative treatment for OSA. Regarding attitudes, 88.7% of the students agreed that OSA as an important clinical disease. Only 7.2% were confident in identifying OSA patients, while 15.5% were confident in managing OSA. Conclusion: The level of OSA knowledge and awareness among dental students in USM was relatively low. Early education and training on OSA in dental schools are crucial to improve this state of affairs. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 384-390